Antioxidant and chemoprotective properties of Momordica charantia L. (bitter melon) fruit extract - Semiz, Aslı.; Sen, Alaattin. (2007)
Momordica charantia, commonly known as bitter melon, is used as a vegetable in number of countries. Extracts of M. charantia plant, fruit pulp, and seed have been reported to have a wide medicinal use in the traditional medical systems, most often as hypoglycemic and anti-diabetic agents. We have studied the effect of M. charantia, collected from Kazdaglari (Mount Ida) in Balikesir, fruit extract on glutathione S-transferases (GSTs), cytochrome P450s (CYPs), and antioxidant enzymes in rats. Male Wistar rats, aged 12 weeks and weighing 200-250 g, were given 200 mg M. charantia fruit extract per kg body weight, i.p., for four consecutive days. At the end of the experimental period, the animals were sacrificed, and liver, kidney, and lung were isolated. Our results have indicated significant increase in especially hepatic antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) activities. The strongest increase (about 9-fold) was observed in GPx activities while about 2 to 5-fold increases were observed in SOD and CAT. M. charantia fruit extract also exhibited hepatoprotective effects in CCl4-intoxicated rats. In addition, about 50% increase was also noted with hepatic cytosolic GSTs. On the other hand, treatments of rats with M. charantia significantly reduced both ethoxyresorufin O-deethylase (EROD) and methoxyresorufin O-deethylase (MROD) activities in rat liver microsomes, which are known to be catalyzed by CYP1A isoforms These results suggest that the M. charantia fruit extract possesses the anti-oxidant effects besides having protective activities in rats. © 2007 Academic Journals.